PENGARUH SERVICE QUALITY, SATISFACTION, DAN PERCEIVED SWITCHING COST TERHADAP CUSTOMER LOYALTY OPERATOR SELULER - Tommy Setiawan Ruslim; Henryanto Wijaya; Halim Putera Siswanto; Hadi Cahyadi (STIE Wiyatamandala, 2020)
The need for cell phone use can be said to be a necessity that cannot be avoided anymore in this day and age, both its use in communicating in business needs, personal needs to social relations with others. The importance of maintaining customer loyalty is very significant to the survival of a company, to maintain customer loyalty many variables that can influence it. This study examines the effect of service quality, customer satisfaction, perceived switching cost on customer loyalty of